Micro and Nanomechanics, Volume 5 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Starman, La Vern.; Hay, Jennifer; Karanjgaokar, Nikhil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Micro-and Nanomechanics, Volume 5 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fifth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: MEMS: Materials & Interfaces Microscale & Microstructural Effects on Mechanical Behavior Novel Nano-scale Probes Nanoindentation & Beyond Nanomechanics Dynamic Micro/Nano Mechanics.
1 A Stochastic Multi-scale Model For Predicting MEMS Stiction Failure -- 2 Full-field Identification of Interfaces in Microelectronic Devices -- 3 Experimental Study of Microstructure and Mechanical Property of Cu30Zn6Al Alloys -- 4 Boundary Mechanics in Lath Martensite, Studied by Uni-axial Micro-tensile Tests -- 5 Evaluating Indent Pile-Up with Gold Films on Non-Plastically Deforming Substrates -- 6 Investigation of Size Effect Through In-Situ SEM Testing of Polystyrene Micropillars -- 7 Temperature and Thickness Dependent Mechanical Properties of Ti Ni Multilayer Thin Films -- 8 A Novel Microdevice for in Situ Study of Mechano-electrochemical Behavior with Controlled Temperatures -- 9 High-Rate Micro-Compression Using an Elastic Half-Space Loading Configuration -- 10 Broadband Electromechanical Spectroscopy A Method for Measuring the Dynamic Electromechanical Response of Ferroelectrics -- 11 Dynamics of Microscale Granular Crystals.
Keywords: Mechanics, Applied; Nanotechnology; Engineering Mechanics; Nanotechnology